Emerging issues in Bangladesh economy : a review of Bangladesh's development, 2005-06. - Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press, 2008)
Contributed articles on Bangladesh economic policy.
Includes bibliographical references.
Economics
Keywords: Bangladesh -- Economic policy; Bangladesh -- Economic conditions